Investigating Thermal Comfort and User Behaviors in Outdoor Spaces: A Seasonal and Spatial Perspective - Kuo-Tsang Huang; Tzu-Ping Lin; Hsiao-Chi Lien (Advances in Meteorology)
Numerous studies have examined the correlation between the number of attendants in a given outdoor environment and thermal indices to understand how the environmental planning has an impact on the users. However, extensive observations should be conducted to examine the detailed static and dynamic behavior patterns of users. We conducted dynamic observations at a stepped plaza to perform on-site measurements of the physical environment and observations of users behaviors, including their resting positions, movements, and stay durations. The results indicated that more people rested on the steps during the cool season than hot season. Compared to neutral temperatures, people demonstrated higher heat tolerance to the hot season. The results indicated that more than 75% of users preferred to remain in shaded areas and stayed longer than in the sunlight. The people tended to engage in static activities in environments that exhibit sufficient shading. The shaded areas were conducive to static activities as the summer grew hotter. The results verified that the people of Taiwan would avoid sunlight and desire shaded spaces based on their previous climate experiences and expectations, which can serve as a reference for outdoor space design to improve the usability and quality of open urban spaces.